Sublethal impacts of pyriproxyfen on biological traits of non-target species, Drosophila melanogaster (Diptera: Drosophilidae) (Bioagro, 2025)
Pyriproxyfen, a juvenile hormone analog (JHA), is considered as reduced-risk alternative to synthetic pesticides for crop protection. It has been frequently used in agriculture and public health to manage insect pests.  However, recent studies have reported that pyriproxyfen may have adverse physiological effects on non-target organisms. This study investigated the effects of sublethal doses of the endocrine disrupting insecticide pyriproxyfen on Drosophila melanogaster Meigen (Diptera: Drosophilidae) as a non-target and biological model. Results showed that pyriproxyfen had a noticeable effect on developmental stages of the individuals of the exposed generation. Pyriproxyfen treatment significantly shortens adult longevity of both sexes, female and male. Finally, these results suggest that reproduction capacity in D. melanogaster is impacted by reducing the number of progeny after the parent’s generation treatment with pyriproxyfen. These research findings indicate that sublethal exposure to pyriproxyfen induces adverse physiological effects and affects offspring growth rates in non-target insects of Drosophila.
Keywords: Drosophila melanogaster; longevity; non-target insect; offspring development; pyriproxyfen